2012
DOI: 10.1093/humrep/des292
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs related to angiogenesis are dysregulated in endometrioid endometrial cancer

Abstract: This work was supported by research grants from the Plan Nacional de Investigación Científica, Desarrollo e Innovación Tecnológica (Instituto de Salud Carlos III, Fondo de Investigación Sanitaria, PI080185, PI0110091) and Red RECAVA (RD06/0014/0004), by Consellería de Sanidad (AP-141/11) and Consellería de Educación (PROMETEO/2011/027), Generalitat Valenciana, by Beca Fibrinolisis 2009 and Becario 2010, 2011 from Fundación Española de Trombosis y Hemostasia and by the Fundación Investigación Hospital La Fe, Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 64 publications
4
37
0
Order By: Relevance
“…Inconsistent results have been reported for the role of miR-17 so far. While some investigatory approaches hypothesize an anti-angiogenetic activity (41,51), other studies account for either pro-angiogenetic activity (83,84) or no association with VEGF-A expression (65). Our data identified a significant hypoxia-driven expression reduction of miR20a in Ishikawa cells.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Inconsistent results have been reported for the role of miR-17 so far. While some investigatory approaches hypothesize an anti-angiogenetic activity (41,51), other studies account for either pro-angiogenetic activity (83,84) or no association with VEGF-A expression (65). Our data identified a significant hypoxia-driven expression reduction of miR20a in Ishikawa cells.…”
Section: Discussionmentioning
confidence: 46%
“…Anti-angiogenetic activity of miR-20a by targeting VEGF-A has been reported (41,65). Inconsistent results have been reported for the role of miR-17 so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age-standardised incidence is 9.1 per 100,000 women per year in more developed countries, compared with 1.7 per 100,000 per year in less developed countries (3). The dysregulation of oncogenes and/or tumor suppressors has been demonstrated to serve a role in EC metastasis (1,4). Therefore, the development of potential molecular targets indicates promise for the treatment of EC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Otsuka et al (31) studied the luteal functions of infertile mice, and further demonstrated that miR-17-5p could affect the endothelial cell functions via the inhibition of metalloproteinase 1 (TIMP-1), thus promoting angiogenesis. Furthermore, previous studies have indicated that miR-17-5p plays a role in the promotion of angiogenesis (32,33). However, previous studies regarding the angiogenic promotion effects of miR-17-5p have not investigated its expression in wounds.…”
Section: A B C D a B Cmentioning
confidence: 99%